STUDI TIPE RUMAH GADANG DAN PENEMPATAN MOTIF UKIR PADA KAWASAN SARIBU RUMAH GADANG DI NAGARI KOTO BARU KABUPATEN SOLOK SELATAN - DOSI YULINA FITRI, Drs. Erfahmi, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (Universitas Negeri Padang, 2016)
The purposes of research are describing: 1) types of rumah gadang 2) placements of wood carving 3) differences of wood carving placement atrumah gadang gonjong anam baanjuang and rumah gadang gonjong tujuah. Theory that used are theory about culture, rumah gadang, types of rumah gadang, carving, tradition, and placements.This research using qualitative method with descriptive approach. Type of data are primary and secondary data which the source of primary data is getting directly from informan statements while secondary data from the books and study literature, data are collecting through observation, interview, and documentation.Kata Kunci: Tipe dan Penempatan Motif Ukir